2021
DOI: 10.1152/japplphysiol.01012.2020
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced fluid shifts are distinct to exercise mode and intensity: a comparison of blood flow-restricted and free-flow resistance exercise

Abstract: Aim: MRI can provide fundamental tools in decoding physiological stressors stimulated by training paradigms. Acute physiological changes induced by three diverse exercise protocols known to elicit similar levels of muscle hypertrophy were evaluated using muscle functional magnetic resonance imaging (mfMRI). Methods: The study was a cross-over study with participants (n=10) performing three acute unilateral knee extensor exercise protocols to failure and a work matched control exercise protocol. Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
3
1
Order By: Relevance
“…We also report declines in knee extensor torque and elevations in CK concentrations that appear to remain at the 24-hr post-race timepoint, and acute increases in leukocyte number, plasma IL-6, and calprotectin concentrations that return to pre-race levels within 24 hrs. While prolonged low-load exercise protocols contribute to muscular swelling or edema [28], this was not observed as greater resting rectus femoris MT following the 50km in our study. Elevation changes, especially elevation loss, can increase muscle swelling and inflammation due to the repeat eccentric contractions that occur during a race with large elevation loss [29].…”
Section: Discussioncontrasting
confidence: 77%
“…We also report declines in knee extensor torque and elevations in CK concentrations that appear to remain at the 24-hr post-race timepoint, and acute increases in leukocyte number, plasma IL-6, and calprotectin concentrations that return to pre-race levels within 24 hrs. While prolonged low-load exercise protocols contribute to muscular swelling or edema [28], this was not observed as greater resting rectus femoris MT following the 50km in our study. Elevation changes, especially elevation loss, can increase muscle swelling and inflammation due to the repeat eccentric contractions that occur during a race with large elevation loss [29].…”
Section: Discussioncontrasting
confidence: 77%
“…However, at 80‐100% of exercise time, this effect seems to be equalled out by the effect of BFR. Interestingly, the changes in Δ[HHb] in VL was not replicated in VM, possibly due to intermuscular differences in muscle excitability or degree of BFR (Haddock et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Blood flow restriction (BFR) is achieved by applying an external pneumatic tourniquet at the proximal end of the upper or lower extremity, applying an occlusion pressure promoting ischemia and blood pooling in the capillary beds of the musculature distal to the tourniquet. 15 The combination of ischemia and mechanical tension during exercise creates an environment of mechanotransductive and metabolic stress in the exercising myofibers 16,17 promoting hypertrophic and strength adaptations. 16,18 Previous meta-analyses have concluded that LL-BFRE may be less effective than HL-RE 19 in increasing maximal muscle strength, but superior to LL-RE without BFR for increasing muscle size and strength.…”
Section: Introductionmentioning
confidence: 99%